2021
DOI: 10.1002/pssb.202000597
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Stability, Elastic Properties, and Electronic Structure of Mg2Si Doped with Different Concentrations of Cu: A First‐Principles Calculation

Abstract: Herein, the effects of Cu doping with different concentrations on the stability, elastic properties, and electronic structure of Mg2Si are investigated by first‐principles calculations based on density functional theory. The research results show that Mg2Si and Mg8−xSi4−yCux+y (x, y) = {(0.125, 0), (0, 0.125), (0.25, 0), (0, 0.25), (0.5, 0), (0, 0.5), (1, 0), (0, 1)} are stable in the system. The Cu atoms tend to preoccupy Mg sites in Mg2Si lattices, and the alloying ability is stronger than that of Mg8Si4−yCu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The Voigt and Reuss models provide the upper and lower bounds of the effective modulus, respectively. The arithmetic average of the two models, known as the Voigt‐Ruess‐Hill approximation, [ 32 ] yields a more accurate estimate of the volume and shear moduli. Table 4 shows the calculated values of these moduli using the Voigt‐Ruess‐Hill approximation, as given by the following equations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Voigt and Reuss models provide the upper and lower bounds of the effective modulus, respectively. The arithmetic average of the two models, known as the Voigt‐Ruess‐Hill approximation, [ 32 ] yields a more accurate estimate of the volume and shear moduli. Table 4 shows the calculated values of these moduli using the Voigt‐Ruess‐Hill approximation, as given by the following equations.…”
Section: Resultsmentioning
confidence: 99%
“…The OTFG ultrasoft [ 29 ] pseudopotential was used to describe the interaction between electrons and ions. The general gradient approximation (GGA+U) and Perdew‐Burke‐Ernzerhof (PBE) [ 32 ] methods were employed to estimate the exchange and correlation energies. Monkhorst‐Pack k‐point grid integration was used to integrate the Brillouin zone.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Based on the first‐principle calculation, [ 14,30 ] the interstitial Mg (I Mg ), interstitial O (I O ), and Mg vacancy (V Mg ) in the lattice of Mg 2 Si are the origins of n‐ and p‐type conduction of samples, that is, the I Mg acts as donor providing electrons, and I O and V Mg act as the acceptors providing holes. Therefore, the conduction type of the sample is the result of the carrier compensation between electrons and holes.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] The results of theoretical calculations showed that undoped Mg 2 Si crystals exhibit n‐type conduction, [ 11,12 ] which is mainly due to the presence of 4b vacancy in the lattice and the easy entry of Mg atoms to generate donor level, [ 10 ] i.e., interstitial Mg atom (I Mg ) leads to n‐type conduction and Mg vacancy (V Mg ) leads to p‐type conduction in Mg 2 Si lattice. [ 10,13,14 ] This means that decreasing I Mg or increasing V Mg during postannealing may cause the sample to become p‐type conduction. [ 15,16 ] Ogawa et al [ 17 ] reported that some of as‐deposited undoped Mg 2 Si films showed n‐type, and the others showed p‐type conduction at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Mg 2 Si has been widely used in many fields due to its attractive properties such as thermoelectric, optoelectronic, electrochemical, and mechanical ones. To improve these properties, especially the thermoelectric property, different elements were doped into Mg 2 Si, such as Ag, [6] B, [7] Bi, [8,9] Cu, [10] Li, [11] P, [12] Sb, [13,14] Y, [15] rare earth elements, [16] and codoped strategy. [17,18] Undoped Mg 2 Si is well known as a nonmagnetic semiconductor.…”
Section: Introductionmentioning
confidence: 99%